A Facile Strategy for Selective Incorporation of Phosphoserine into Histones1. Issue 22 (26th March 2013) - Lee, Sangsik; Oh, Seunghee; Yang, Aerin; Kim, Jihyo; Söll, Dieter; Lee, Daeyoup; Park, Hee‐Sung
<x xml:space="preserve">Abstract</x> Phosphoserine incorporation: A general strategy for producing recombinant histones with site‐specific serine phosphorylation is developed by engineering phosphoseryl‐tRNA synthetase (SepRS) and elongation factor Tu (EF‐Tu; see picture). Serine‐phosphorylated nucleosomes provide direct evidence for crosstalk between phosphorylation and acetylation in histones.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>